Music as multimodal discourse : semiotics, power and protest - Way, Lyndon C. S.; McKerrell, Simon; Way, Lyndon C. S. (b)
This book considers musical sound as multimodal communication, examining the interacting meaning potential of sonic aspects such as rhythm, instrumentation, pitch, tonality, melody and their interrelationships with text, image and other modes